Mapping Research on Financial Institution Cash Flow Analysis: A Bibliometric Analysis - Rahmadani Aidil Fitrohcahya; Dzaki Muqaffa (CV. Megantara Abdi Nusa, 2025)
This study aims to analyze the cash flows of financial institutions through a bibliometric approach, using secondary data from income statements and cash flow statements. Financial institutions, which consist of bank and non-bank financial institutions, play an important role in the stability of the financial system in Indonesia. The bibliometric analysis method was applied to evaluate the pattern of scientific publications related to cash flow, identifying trends, challenges and opportunities in financial management. The data used includes scientific publication articles from accredited national journals within the time span of 2014 to 2024. The results showed that there were 79 articles published, with visualization mapping dividing the research into 5 clusters and 17 items. This research suggests that future studies use a wider data sample and a longer time span to obtain a more comprehensive and complex mapping in the field of cash flow of financial institutions.